Preoperative serum indicators as predictors of postoperative hypoparathyroidism following thyroidectomy - Liu, Kailin; Wang, Nana; Zhao, Peng; Zhao, Baoyan; Wang, Zhihao; Sun, Yongjie; Geng, Chong (Frontiers in Endocrinology, 2025)
BackgroundHypoparathyroidism is a frequent complication following thyroidectomy. However, the risk factors for postoperative hypoparathyroidism remain poorly characterized. This study aims to investigate routine clinical characteristics to identify predictors of postoperative hypoparathyroidism.MethodsA retrospective analysis was conducted on 3,638 patients who underwent total or hemithyroidectomy with isthmusectomy through open surgery with routine central lymph node dissection. Based on postoperative serum parathyroid hormone(PTH) levels, patients were subdivided according to the normal reference PTH levels or the Q3 quartile of PTH decline rate. Spearman correlation analysis and stepwise multiple linear regression were used to identify factors affecting preoperative serum PTH levels. Univariate and multivariate logistic regression analyses were performed to explore risk factors for postoperative hypoparathyroidism.ResultsAmong patients developed postoperative hypoparathyroidism. Multivariate logistic regression revealed that Hashimoto’s thyroiditis (HT) (OR=1.786, P=0.007) and preoperative blood glucose (OR=1.319, P=0.005) was an independent risk factor, while body mass index (BMI)≥24 (OR=0.714, P=0.032),elevated preoperative PTH levels (OR=0.988, P=0.013)and male (OR=0.554, P=0.002) were protective factors. Among patients in the Q3 quartile,postoperative PTH decline rate was positively associated with HT (OR=2.266, P<0.001), preoperative PTH levels (OR=1.032, P<0.001), and blood glucose (OR=1.234, P=0.027), while it was negatively associated with BMI≥24 (OR=0.611, P=0.013), hemoglobin (OR=0.984, P=0.003), and high-density lipoprotein cholesterol (HDL-C) (OR=0.426, P=0.007).Additionally, male (OR=0.558, P=0.003) and preoperative serum Ca2+ levels (OR=0.110, P=0.011) were negatively correlated with the postoperative PTH decline rate in patients undergoing hemithyroidectomy with isthmusectomy. Furthermore, age had no significant effect on the incidence of postoperative hypoparathyroidism.ConclusionsThis study demonstrates that preoperative high glucose levels and HT are risk factors for hypoparathyroidism after total thyroidectomy, while BMI≥24 serves as a protective factor against postoperative hypoparathyroidism. Additionally, female is a risk factor for hypoparathyroidism after both total thyroidectomy and hemithyroidectomy with isthmusectomy, while higher hemoglobin levels and HDL-C are negatively correlated with the decline in PTH levels after total thyroidectomy.